Frequency distribution of mRNA and pre-mRNA in growing and differentiated Friend cells. - Mauron, A (1978)
The frequency distribution of poly(A)+-mRNA in growing and in differentiated Friend cells has been measured by mRNA-cDNA hybridization and their differences established by heterologous hybridization of mRNA of one type and cDNA of the other. It was shown that induction of Friend cells involves an increase in abundance of a small number of mRNAs, while no specific pattern of messenger disappearance could be detected. The frequency distribution of pre-mRNA was determined by hybridizing nuclear RNA with the cDNA probes complementary to mRNA. In uninduced Friend cells, it was shown that most precursor messenger sequences are present at a single frequency of about 3 molecules per nucleus, independently of their final frequency in polysomal mRNA. In induced Friend cells, the frequency distribution of pre-mRNA is more heterogeneous and correlated to some extent with the corresponding mRNA frequency distribution.